2018
DOI: 10.1159/000487204
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA UCA1 Is a Novel Regulator in Cardiomyocyte Hypertrophy through Targeting the miR-184/HOXA9 Axis

Abstract: Cardiac hypertrophy is closely associated with a series of cardiovascular diseases, including heart failure and sudden death in particular. An in-depth comprehension of the pathogenesis of cardiac hypertrophy will improve the diagnosis and therapy of cardiac hypertrophy. It has been acknowledged that long noncoding RNAs/microRNAs (lncRNAs/miRNAs) are crucial regulators in diverse biological processes, including various cardiovascular diseases, in multiple manners. Nevertheless, the biological roles of lncRNA U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
(32 reference statements)
0
31
0
1
Order By: Relevance
“…The heart‐specific lncRNA Chaer was reported to interact with PRC2, contributing to the activation of pathological cardiac hypertrophy genes (Wang et al, ). lncRNA UCA1 was confirmed to be an activator in cardiomyocyte hypertrophy responses via modulating miR‐184 (G. Zhou, Li, Feng, Zhang, & Fang, ). lncRNA XIST is located on the X chromosome in the X‐inactivation center (Brockdorff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The heart‐specific lncRNA Chaer was reported to interact with PRC2, contributing to the activation of pathological cardiac hypertrophy genes (Wang et al, ). lncRNA UCA1 was confirmed to be an activator in cardiomyocyte hypertrophy responses via modulating miR‐184 (G. Zhou, Li, Feng, Zhang, & Fang, ). lncRNA XIST is located on the X chromosome in the X‐inactivation center (Brockdorff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR‐15a‐5p is found to be upregulated in plasma of hypertrophic cardiomyopathy patients (Fang et al, 2015). Simvastatin attenuates cardiomyocytes apoptosis by inhibiting miR‐15a‐5p and then increasing Bcl‐2 (Zhou et al, 2018a,b). These evidences suggest that miR‐15a‐5p might be a crucial regulator to mediate cardiac functions.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analysis revealed that PSG10P can promote the expression of IL1RAP by sponging miR‐19a‐3p. Many studies have been performed on the interactions among RNA molecules, such as interactions between lncRNA‐miRNA and miRNA‐mRNA . Here, we focused on the interaction between PSG10P‐miR‐19a‐3p and miR‐19a‐3p‐ IL1RAP .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed on the interactions among RNA molecules, such as interactions between lncRNA-miRNA and miRNA-mRNA. 24,25 Here, we focused on the interaction between PSG10P-miR-19a-3p and miR-19a-3p-IL1RAP. In addition, we hypothesized that the PSG10P/ miR-19a-3p/IL1RAP network regulates the growth and invasion of trophoblastic cells under hypoxia.…”
Section: Introductionmentioning
confidence: 99%